Challenges in access to healthcare from the perspective of people in street situations (Research, Society and Development, 2022)
The existing social inequality in Brazil, aggravated by the situation of extreme poverty, contributes significantly to the increase in the Homeless Population (PSR). The research aimed to identify the main difficulties of homeless people in accessing public health policies. Methodology: this is a qualitative study, carried out through eight semi-structured interviews, with the target audience of homeless people in Amapá, Macapá. For data analysis, content analysis was used in the thematic modality. Results: drug use, family conflicts, moving to another state and unemployment were the reasons that led them to the streets. It was observed that 37.5% of respondents have been homeless for more than 10 years and, consequently, many ended up breaking family ties. It was evidenced that drug use is not always the reason that leads to homelessness, but its consumption is common, aggravating the health and social condition of the individual. Conclusion: it is concluded that it is necessary to create and implement Public Policies aimed at this public, aiming at rehabilitation and social reintegration.